938. Identifying Gaps in the Treatment of Hepatitis C in Patients Co-Infected with HIV in Edmonton, Alberta. (31st December 2020) - Savaryn, Bohdan; Round, Jessica; Plitt, Sabrina; Shafran, Stephen; Charlton, Carmen
Abstract: Background: The Northern Alberta HIV Program (NAHP) provides care and support for about 2500 HIV positive individuals. Part of the program includes screening and therapy for co-morbidities such as hepatitis C virus (HCV) infection. This study aims to assess the occurrence of HCV co-infection among these patients, determine whether they had received treatment for HCV, and identify patients who are currently viremic so they can be linked to care. Methods: NAHP patients from 2010 to 2019 were linked to their HCV antibody, RNA, and genotyping laboratory testing data from January 1, 2000 to December 31, 2019 as well as HCV medication dispensation data. Each patient's current and previous state of HCV infection and treatment status was assessed. Chart reviews were conducted for patients presently HCV viremic to assess their HIV care and social determinants. Results: Of the 2417 NAHP patients, 392 (16.2%) were identified as having been co-infected with HCV at some point between January 1, 2000 to December 31, 2019 and meeting the inclusion criteria. Overall, 198 (50.5%) of the HIV-HCV co-infected patients had received HCV treatment and 232 (59.2%) were no longer viremic at their most recent HCV RNA test. 99 (69.2%) of the 143 HCV viremic patients had a suppressed HIV infection suggesting they are active in their HIV care and good candidates for HCV treatment. Figure 1. 2417 patients in the Northern Alberta HIV Program were evaluated for the presence of an HIV- HCV co-infection. 404 patients were identified as having been HIV-HCV co-infected at some point between January 1, 2000 and December 31, 2019. Figure 2. 404 HIV-HCV co-infected patients from the Northern Alberta HIV Program were assessed for the occurrence of treatment as well as the current status of their HCV infection. 143 patients were found to currently have an active HIV-HCV co-infection. Table 2. Characteristics of HIV-HCV co-infected patients from the NAHP with an active HCV infection (n=143) Conclusion: The NAHP has been successful in identifying and treating many of their HIV HCV co-infected patients, however, there remain patients with viremic HCV. Despite the availability of direct-acting antivirals (DAAs) in Alberta and many of these patients being successfully treated for HIV, a significant proportion of co-infected patients have not initiated HCV treatment The HIV treating physicians of these individuals will be notified and encouraged to assist in getting them linked to HCV care and treatment. Disclosures: All Authors : No reported disclosures